Online Identification of Synchronous Generator Electromechanical Parameters for Intelligent Control Problems - Frolov M.Yu.; Stepanovich R. Yu.; Lizalek N.N.; Dulov I.V. (Problems of the Regional Energetics, 2022)
The control system intelligence is determined by the ability to adapt to changing circuit-mode parameters. This approach is especially relevant for emergency automation, because the emer-gency depends on the huge number of factors. In addition, an accident can develop in cascade, causing uncontrolled and multiple changes in the grid topology and mode parameters. The for-mation of the control actions volume of emergency automatics is carried out on the basis of the computing of the mode on mathematical models of electrical grids, the accuracy of which de-termines the adequacy of the actions of automation, so the models verifying problem arises, in-cluding electromechanical parameters determining of the grid elements. The aim of the research is to develop methods for parameter identification of synchronous generators. The paper pre-sents two methods for identifying the synchronous generator constant inertia and the method for identifying the synchronous inductive resistance. The research of the proposed methods was carried out on the digital model assembled in MatLab Simulink, where the 200 MVA 13.8 kV generator was simulated. In addition, the research was performed using the physical electrody-namic model. The parameters of the generator 3000 VA 230 V were determined. The results of parameters determining by the classical methods of open-circuit and short-circuit are presented. The significance of these methods is that the generator is connected to the grid and is in an op-eration mode. This will make possible to form and refine the model online in accordance with the circuit-mode situation, which will increase the control actions adequacy.